What is the burden of multimorbidity and the factors associated with its occurrence in elderly Brazilians? - Danielle Samara Tavares de Oliveira-Figueiredo; Matteus Pio Gianotti Pereira Cruz Silva; Paula Yhasmym de Oliveira Feitosa; Bruna Cardoso Leite; Fabiana Lucena Rocha; Luciana Dantas Farias de Andrade (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To estimate the prevalence of multimorbidity in elderly people and its association with sociodemographic characteristics, lifestyle, and anthropometry. Methods: This was a cross-sectional study using data from the National Health Survey, 2019. A total of 22,728 elderly individuals from all 27 Brazilian states were randomly selected. Poisson regression models with robust variance were employed, and a significance level of 5% was adopted. Results: The prevalence of multimorbidity was 51.6% (95% CI: 50.4-52.7), with the highest estimates observed in the South and Southeast. Multimorbidity was associated with being female (aPR = 1.33; 95% CI: 1.27-1.39), being 80 years old or older (aPR = 1.12; 95% CI: 1.05-1.19), having low education (aPR = 1.16; 95% CI: 1.07-1.25), past cigarette use (aPR = 1.16; 95% CI: 1.11-1.21), insufficient physical activity (aPR = 1.13; 95% CI: 1.06-1.21), and screen use for 3 hours or more per day (aPR = 1.13; 95% CI: 1.08-1.18). Conclusion: Multimorbidity affects more than half of the elderly population in Brazil and is associated with social, demographic, and behavioral factors.